Association Genetics of the Cinnamyl Alcohol Dehydrogenase (CAD) and Cinnamate 4-hydroxylase (C4H) Genes with Basic Wood Density in Neolamarckia cadamba - Ho, Wei Seng; Tchin, Boon Ling; Pang, S.L; Ismail, Jusoh (Science Alert, 2012)
Association genetics study is a powerful approach to detect the potential genetic variants (i.e., SNPs) underlying the common and complex adaptive traits. Once the quantitative trait nucleotides are identified, such powerful approach provides significant advantages to the forest industry. Hence, attempts were made to discover SNPs from Neolamarckia cadamba partial C4H (3,538 bp) and CAD (2,354 bp) DNA sequences and further associate those SNPs with basic wood density. Overlapping primers were designed in flanking the partial C4H and CAD DNA from 12 N. cadamba trees. The amplified DNA fragments were sequenced and the basic wood density measurements were determined for each tree. The sequence variation analyses revealed that there were 60 and 32 SNPs detected in the partial C4H and CAD DNA sequences, respectively. Those SNPs were distributed throughout the exon, intron, 5’-UTR and 3’-UTR regions. The total nucleotide diversities were π = 0.00302 and θW = 0.00412. The synonymous mutations (π = 0.00983; θW = 0.01210) were more common than nonsynonymous mutations (π = 0.00045; θw = 0.00089) for both C4H and CAD genes. LD declined linearly over short distance at the loci examined. Association genetics study also revealed that 4 and 6 SNPs from C4H and CAD genes, respectively were in significant associations with basic wood density of N. cadamba (p<0.05). The genetic variation identified by the SNP markers, once validated, will facilitate the selection of N. cadamba parental lines or seedlings with optimal quality through Gene-assisted Selection (GAS) approach.